Conserving Local Knowledge In Traditional Healing Through Knowledge Transfer - Che Lah, Salasiah; Esa, Norizan; Rajamani, Leila; Mohamed, Baharuddin; Bidin, Mohamad Omar; Osman, Omar; Wan Talaat, Wan Izatul Asma (EDP Sciences, 2015)
Local knowledge (LK) basically refers to the knowledge that people in a given community have developed over time, and continues to develop, through practices and based on experiences. Local beliefs pertaining to ilmu, a central concept in Malay culture that refers to knowledge, is essential among the traditional healers. The vast repository of knowledge and its relevance to locality and local situation makes the conservation of LK a necessity.However, due to the dominance of modern knowledge, diminished inter-generational knowledge transfer has led to LK being threatened with extinction. The fact that LK is practiced by only a few these days could be due to lack of knowledge transfer to the younger generations from the traditional healers who are knowledgeable in the communities. The common transfer mode of local knowledge, usually via words of mouth, may not be sustainable because the LK could vanish when knowledgeable elders die before it is transferred or during resettlements of individuals or communities. The need to conserve LK through knowledge transfer is also pertinent for the continued sustenance of their culture by recognizing, protecting and enforcing the rights of local communities to have continued access to biological resources as well as by protecting their LK, acquired over thousand of years of experimentation and experience, about the uses of these biological resources in traditional healing. Therefore, it is important to have a governance framework to effectively protect this LK of the local communities for the continued sustenance of their culture. This conceptual paper attempts to highlight the significance of conserving LK in traditional healing via effective knowledge transfer method, which should thereafter be translated into a working governance framework that protects the knowledge as well as the holders of such knowledge.